Soluble antigen arrays provide increased efficacy and safety over free peptides for tolerogenic immunotherapy - Firdessa-Fite, Rebuma; Johnson, Stephanie N.; Bechi Genzano, Camillo; Leon, Martin A.; Ku, Amy; Ocampo Gonzalez, Fernando A.; Milner, Joshua D.; Sestak, Joshua O.; Berkland, Cory; Creusot, Remi J. (Frontiers in Immunology, 2024)
Autoantigen-specific immunotherapy using peptides offers a more targeted approach to treat autoimmune diseases, but the limited in vivo stability and uptake of peptides impedes clinical implementation. We previously showed that multivalent delivery of peptides as soluble antigen arrays (SAgAs) efficiently protects against spontaneous autoimmune diabetes in the non-obese diabetic (NOD) mouse model. Here, we compared the efficacy, safety, and mechanisms of action of SAgAs versus free peptides. SAgAs, but not their corresponding free peptides at equivalent doses, efficiently prevented the development of diabetes. SAgAs increased the frequency of regulatory T cells among peptide-specific T cells or induce their anergy/exhaustion or deletion, depending on the type of SAgA used (hydrolysable (hSAgA) and non-hydrolysable 'click' SAgA (cSAgA)) and duration of treatment, whereas their corresponding free peptides induced a more effector phenotype following delayed clonal expansion. Over time, the peptides induced an IgE-independent anaphylactic reaction, the incidence of which was significantly delayed when peptides were in SAgA form rather than in free form. Moreover, the N-terminal modification of peptides with aminooxy or alkyne linkers, which was needed for grafting onto hyaluronic acid to make hSAgA or cSAgA variants, respectively, influenced their stimulatory potency and safety, with alkyne-functionalized peptides being more potent and less anaphylactogenic than aminooxy-functionalized peptides. Immunologic anaphylaxis occurred in NOD mice in a dosedependent manner but not in C57BL/6 or BALB/c mice; however, its incidence did not correlate with the level of anti-peptide antibodies. We provide evidence that SAgAs significantly improve the efficacy of peptides to induce tolerance and prevent autoimmune diabetes while at the same time reducing their anaphylactogenic potential.